The Origin of Developmental State in Singapore - Irawan, Diandini Rahmawati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2017)
This essay describes the origin of developmental state in Singapore. What characteristic that Singapore has as a developmental state that can support their economic growth and political stability. This article uses a qualitative approach which data collection techniques are literature studies. This article will analyze the circumstances in which developmental state emerges. It will argue the relevancies in using the developmental state concept as an alternative solution in gaining rapid socio economic growth. My contention is that the developmental state notion is still relevant in order to explain about the changing strategy in industrial policies. Moreover, the successful implementation of the developmental state will be continue if Singapore can deliver socioeconomic growth while at the same time it can manage class relation in society. Esai ini menggambarkan asal mula perkembangan negara di Singapura. Karakteristik apa yang dimiliki Singapura sebagai negara berkembang yang dapat mendukung pertumbuhan ekonomi dan stabilitas politik mereka. Artikel ini menggunakan pendekatan kualitatif yang teknik pengumpulan datanya adalah studi pustaka. Artikel ini akan menganalisis keadaan dimana negara berkembang muncul sebagai bantahan relevansi dalam menggunakan konsep pembangunan negara sebagai solusi alternatif dalam mendapatkan pertumbuhan ekonomi sosial yang cepat. Kesimpulannya saya adalah bahwa gagasan negara berkembang masih relevan untuk menjelaskan tentang strategi perubahan dalam kebijakan industri. Apalagi, keberhasilan implementasi pembangunan negara akan terus berlanjut jika Singapura dapat memberikan pertumbuhan sosial ekonomi sementara pada saat yang sama dapat mengelola hubungan kelas di masyarakat.